1999
DOI: 10.1046/j.1469-8137.1999.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen‐tube growth rate and seed‐siring success among Betula pendula clones

Abstract: The aim of this study was to investigate whether genetically different pollen donors (Betula pendula clones) differed in pollen-tube growth rate across 11 maternal plants and in vitro, and whether the differences between the donors were consistent across the recipients. To compare the seed-siring success of competing pollen donors, a two-donor hand-pollination experiment with six donors and six recipients was conducted. The experiments were performed at a plastic-house seed orchard. The donors showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 59 publications
3
55
1
1
Order By: Relevance
“…For statistical testing, we transformed the proportion of seeds sired by Col-NPTII in each individual cross using an arcsine square root transformation. We then used these numbers to perform an independent t test sires, an idea supported by quite a few studies (Levin 1975;Pasonen et al 1999;Skogsmyr and Lankinen 1999;Spira 1991a, b, 1996). Many pollen tube growth studies are performed in vitro, in pollen growth medium.…”
Section: Pollen Germination: Quantifying Pollen Germination Efficiencymentioning
confidence: 99%
“…For statistical testing, we transformed the proportion of seeds sired by Col-NPTII in each individual cross using an arcsine square root transformation. We then used these numbers to perform an independent t test sires, an idea supported by quite a few studies (Levin 1975;Pasonen et al 1999;Skogsmyr and Lankinen 1999;Spira 1991a, b, 1996). Many pollen tube growth studies are performed in vitro, in pollen growth medium.…”
Section: Pollen Germination: Quantifying Pollen Germination Efficiencymentioning
confidence: 99%
“…For instance, Pasonen et al (1999) compared the seed-siring success of competing pollen donors in Betula pendula after two-donor hand-pollinations. Seed-siring success was significantly non-random in 20 out of 29 crosses involving six donors and eleven recipient plants selected for their specific isozyme marker.…”
Section: Variation Among Donor Plants In Seed Siring Successmentioning
confidence: 99%
“…However, the use of the Baker reagent to analyze Acacia mearnsii polyad viability was justified by the time savings, since samples with reduced viability could be detected and discarded in an initial analysis. [Brewbaker and Kwack (1963) Variation in pollen grain development was described in Betula pendula clones (Pasonen et al 2000), where a correlation was detected between the in vitro pollen tube growth and seed formation rates. Evidence suggested that male reproductive success was in fact controlled by the mother plant influenced by the pollen grain genotype and that it differed among trees and among pollen grains from the same individual (Snow andSpira 1996, Traveset 1999).…”
Section: In Vitro Germination and Pollen Tube Growthmentioning
confidence: 99%